2011
DOI: 10.1002/bip.21443
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscularly administered peptide A3‐APO is effective against carbapenem‐resistant Acinetobacter baumannii in mouse models of systemic infections

Abstract: Most antibacterial peptides exhibit low therapeutic indices in vivo. Peptide A3-APO was shown to exhibit high potency against Escherichia coli bacteremia when added intraperitoneally. To extend the studies to systemic infections against multidrug-resistant organisms, we studied the efficacy of A3-APO in mouse models of carbapenem-resistant Acinetobacter baumannii infection. When administered either intravenously at 2.5 mg/kg or intramuscularly (im) at 5 mg/kg twice or three times to mice infected with a carbap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Indeed, Gries et al have shown that bacteria with hyperpolarized membranes are more susceptible to cationic antimicrobial peptides (Gries et al, 2013). This mechanism may in part explain the finding that the monomer and A3-APO are more effective in vivo (Ostorhazi et al, 2011a(Ostorhazi et al, , 2011bOtvos et al, 2014;Szabo et al, 2010), as a bacterial infection would induce the release of AMPs from host cells such as neutrophils.…”
Section: Analysis Of Membrane Potentialmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, Gries et al have shown that bacteria with hyperpolarized membranes are more susceptible to cationic antimicrobial peptides (Gries et al, 2013). This mechanism may in part explain the finding that the monomer and A3-APO are more effective in vivo (Ostorhazi et al, 2011a(Ostorhazi et al, , 2011bOtvos et al, 2014;Szabo et al, 2010), as a bacterial infection would induce the release of AMPs from host cells such as neutrophils.…”
Section: Analysis Of Membrane Potentialmentioning
confidence: 91%
“…The branched dimeric form of A3-APO displays extensive and potent activity against Gram-negative bacteria including against MDR microbes in vitro, but also decreases the mortality and bacterial load in mouse models infected by MDR microbes in vivo (Ostorhazi et al, 2011a(Ostorhazi et al, , 2011bOtvos et al, 2014;Szabo et al, 2010). Furthermore, by inhibiting the folding of enzymes responsible for bacterial resistance, A3-APO in combination with conventional antibiotics either partially or fully restores their lost activities against MDR pathogens Cassone et al, 2008;Otvos et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Although the APO peptides have only weak activity against Acinetobacter baumannii in vitro, when administered either intravenously or intramuscularly to mice infected with a carbapenem-resistant A. baumannii strain, the peptides significantly reduce bacterial load and increase survival compared with mice treated with higher doses of imipenem [98]. While the dimer practically does not kill S. aureus or Proteus mirabilis strains in vitro, when administered intramuscularly or as an aerosol, it improves mouse survival and reduces bacterial counts at the infection site and in blood in wound infection or pneumonia models [99].…”
Section: Designer Proline-arginine-rich Antibioticsmentioning
confidence: 99%
“…Although the minimum inhibitory concentration (MIC) of the designer proline-rich antibacterial peptide A3-APO is as high as 16-64 mg/L against most clinical Escherichia coli and Acinetobacter baumannii strains, the in vivo therapeutic dose is 10 mg/kg when administered intraperitoneally and 5 mg/kg when administered intramuscularly [1,2]. A3-APO protects mice better against a multidrug-resistant A. baumannii strain at a 5 mg/kg intramuscular (i.m.)…”
Section: Introductionmentioning
confidence: 99%